So sorry for your loss : how I learned to live with grief, and other grave concerns - Gachman, Dina (Union Square & Co., 2022)
"A searching, heartfelt exploration about what it means to process grief, by a bestselling author and journalist whose experience with two devastating losses inspired her to bring comfort and understanding to others. Since losing her mother to cancer in 2018 and her sister to alcoholism less than three years later, author and journalist Dina Gachman has dedicated herself to understanding what it means to grieve, healing after loss, and the ways we stay connected to those we miss. Through a mix of personal storytelling, reporting, and insight from experts and even moments of humor, Gachman gives readers a fresh take on grief and bereavement--whether the loss is a family member, beloved pet, or a romantic relationship. No one wants to join the grief club, since membership comes with zero perks, but So Sorry for Your Loss will make that initiation just a little less painful"--